Travestis and Transsexuals in the Fantástico Special Report: Male Prison Units are not the “Show of Life” - Dalagostini Bidarte, Marcos Vinicius; Silveira do Canto, Lucas Gabriel; Rodrigues, Maria Beatriz (Organizações & Sociedade, 2023)
In March of 2020, the Sunday program Fantástico aired a special report with the doctor Drauzio Varella on travestis and trans women who have spent years in male prison units in Brazil. This study aims to analyze how these people face prejudice, abandonment, violence, and solitude, conversing with intersectionality by highlighting social markers of difference and with turning points, marking the moment in which something begins to change significantly in the subject’s life story and trajectory. The corpus of this study is constituted of the analysis of texts, images, and videos, with a focus on interpretative and intersectional analyses and on identifying turning points. The strata of life stories discussed here reveal the expression of identities, prejudices, and the discriminations suffered, and so favor the discussion of social privileges and inequalities based on gender and sexual orientation. The expression of these identities oscillates between the circumscribed, artificial world of the prison, which in some way favors an open experience of modes of being and living, and a demonstration of the suffering inflicted by the discrimination of the surrounding society, with its impossibilities of inclusion and its dictates on who can and cannot be accepted.